LITERATURE REVIEW SOFTWARE, COMPANY EFFICIENCY AND EVALUATION OF COMPANY PERFORMANCE - Wydyanto, Wydyanto (Dinasti Publisher, 2022)
In this study, researchers discussed software, efficiency, and evaluation of company performance. Software is an essential component in a hardware company used to carry out business activities and communicate. Then efficiency is an activity carried out by the company to minimize costs incurred to save cash. Then an evaluation is an activity carried out after implementing planning, organization, actuating, and controlling to solve problems or obstacles that occur. This study uses descriptive qualitative methods and library research by collecting data from Google Scholar and using Mendeley as a reference. The results of this study are 1) Software related to company performance, 2) company efficiency related to company performance, and 3) evaluation related to company performance.